Annealing Conditions' Influence on the Oxidation of Silicon‐Aluminium‐Alloys in Combinatorial Thin‐Film Libraries. Issue 12 (6th May 2019) - Niederwimmer, Karin; Mardare, Cezarina Cela; König, Wolfgang T.; Huber, Silvia; Angeli, Gerhard; Hassel, Achim Walter
Abstract : Alloys containing aluminium and silicon are of wide use. Due to their abundance, these elements are promising contributors to technical materials. A combinatorial thin‐film approach (silicon content within 27 at.% and 65 at.%, and aluminium between 35 at.% and 73 at.%, deposited by simultaneous co‐sputtering) is chosen for systematic investigations of reactions and compositions of high‐silicon containing alloys with aluminium. As the melting points of silicon and aluminium are far from each other and, furthermore, the binary system comes along with a eutectic point, high‐temperature stability oxidation of these alloys is of interest. Moreover, due to the high oxygen affinity of both, silicon and aluminium, the stability under different annealing conditions is explored. These annealing conditions provide different partial pressures of oxygen while leaving the remaining parameters constant in order not to superimpose the effect of the annealing atmosphere. Surface imaging, together with chemical analysis and contact potential difference (CPD) by Scanning Kelvin Probe along and across libraries provide an insight into the influence of annealing atmosphere onto the surface properties. However, determining an influence of the deposition method on the results is not subject to this investigation. Abstract : Thin‐film combinatorial libraries (Si between 27 and 65 at.%, Al between 36 and 73 at.%, are annealed at different partial pressure of oxygen (within the range of 10 −1 Pa and 10 −11 Pa). The influence of these different annealing condition is evaluated using different analytical methods with further respect to melting and eutectic point.